"No te conozco, pero aquí estoy" Solidarity letters in times of COVID-19 in Spain - Pilar González-Cervera; Ruben Mirón-González (Universidad Carlos III de Madrid, 2020)
Introduction: April 2020 concluded with more than 80,000 COVID-19 patients hospitalized in Spain. Social isolation is one of the problems derived from the institutionalization. To combat this problem, the project "No te conozco, pero aquí estoy" (NTCPAE) -I don't know you but here I am- emerged, which aimed to receive and send at least 6,000 letters in 36 hospitals and 6 nursing home. Objectives: To identify the motivation of the senders of the letters to participate in the NTCPAE project. Methodology: Cross-sectional, observational and descriptive study. We have designed a 19 self-prepared items questionnaire and we sent 4,820 questionnaires. Results: We have received 2,021 fulfilled questionnaires, of which 89,4% were women. 55,4% reported to have had a close person with COVID-19, and the questions scored higher than 3,8 points out of 5. Discussion: Respondents showed a motivation to participate in the project related to empathy, personal satisfaction and the positive impact on emotional health of the institutionalized person with COVID-19. Conclusions: We consider that the NTCPAE project has helped to materialize the motivation and social commitment of the population for the benefit of the institutionalized person during the COVID-19 pandemic.